lncRNA-KCNQ1OT1: A Potential Target in Exosomes Derived from Adipose-Derived Stem Cells for the Treatment of Osteoporosis - Shan-zheng Wang; Jun Jia; Chang-hong Chen (Stem Cells International)
Background. Osteoporosis is a worldwide medical and socioeconomic burden characterized by systemic impairment of bone strength and microstructure. Exosomes derived from adipose-derived stem cells (ADSCs-Exos) have been confirmed to play effective roles in the repair of various tissues and organs. This study was aimed at investigating the role of ADSCs-Exos and a novel long noncoding RNA KCNQ1OT1 played in osteoporosis as well as the underlying mechanism. Methods. Primary osteoblasts were treated with different doses of tumor necrosis factor-α (TNF-α) (0, 1, 2.5, 5, and 10 ng/ml) and then cocultured with ADSCs-Exos or exosome-derived from lnc-KCNQ1OT1-modified ADSCs (KCNQ1OT1-Exos). The expression of miRNA-141-5p (miR-141-5p) and lnc-KCNQ1OT1 was evaluated by quantitative real-time polymerase chain reaction (qRT-PCR). The protein expression of cleaved-caspase-3, caspase-3, and Bax was determined by Western blot. Cell viability and apoptosis were assessed by Cell Counting Kit-8 (CCK-8) and flow cytometry analysis, respectively. The binding sites between KCNQ1OT1 and miR-141-5p were validated by dual-luciferase reporter assay. Results. TNF-α dose-dependently increased miR-141-5p expression, inhibited viability, and promoted apoptosis of osteoblasts. However, miR-141-5p silencing or cocultured with ADSCs-Exos attenuated these effects. In addition, KCNQ1OT1-Exos could more significantly attenuate the induced cytotoxicity and apoptosis compared to ADSCs-Exos. Moreover, miR-141-5p was confirmed as the target of KCNQ1OT1 by luciferase reporter assay. Conclusions. ADSCs-Exos can attenuate cytotoxicity and apoptosis of TNF-α-induced primary osteoblasts. KCNQ1OT1-Exos have a more significant inhibitory effect compared to ADSCs-Exos by the function of sponging miR-141-5p, suggesting that KCNQ1OT1-Exos can be promising agents in osteoporosis treatment.